ANALISIS EFISIENSI BOILER DENGAN METODE INPUT– OUTPUT DI PT. JAPFA COMFEED INDONESIA Tbk. UNIT BANJARMASIN - Imam Muzaki; Aqli Mursadin (Scientific Journal of Mechanical Engineering Kinematika, 2019)
This paper shows some of the research results. The result of this research shows that the boiler efficiency at operational condition (present) is 79,32% decreased efficiency equal to 9,19% compared with operational condition with efficiency as big as 88,51%. One of the factors analyzing the declining efficiency of the boiler is greatly influencing the heat transfer process, because if there is dirt or crust on the boiler pipe and the fouling, it will result in the process of heat transfer will decrease so that the heat transfer rate will decrease, and will also affect the amount of heat losses in the boiler.